Updates in Anesthesia The Operating Room and Beyond - Ng-Pellegrino, Anna; Stawicki, Stanislaw P. (IntechOpen, 2023)
The word "anesthesia" is commonly associated with surgery in an operating room setting. This book hopes to take the reader on a journey that will highlight the myriad roles that anesthesiologists currently play, and what roles beyond the operating room are on the horizon. In this book, we hope to portray modern anesthesiology as a truly unifying force within the fabric of the contemporary healthcare environment.